Purification and properties of M protein extracted from group A streptococci with pepsin: covalent structure of the amino terminal region of type 24 M antigen - Beachey, EH (The Rockefeller University Press, 1977)
M protein was extracted from type 24, group A streptococci with pepsin at pH 5.8 and was further purified by ammonium sulfate precipitation, ribonuclease digestion, ion-exchange chromatography, and isoelectric focusing. The purified pepsin extract of M (pep M) protein was shown to be free of nontype-specific immunoreactivity in (a) complement fixation tests with heterologous M antiserum, (b) skin tests in normal adult guinea pigs, and (c) passive hemagglutination tests for the presence of lipoteichoic acid sensitizing or antigenic activity. The pep M24 was highly immunogenic; two of three rabbits developed opsonic antibody titers of 1:256 and the third a titer of 1:32 6 wk after a single injection of 100-pg doses of pep M24 emulsified in complete Freund's adjuvant. The antisera lacked nontype-specific antibodies and produced single precipitin lines in agar gel diffusion tests against crude HC1 extracts of the homologous M protein. Thus, the type-specific antigenic determinant(s) of type 24 M protein appears to be separable from immunotoxic, cross-reactive antigens without loss of immunogenicity in rabbits. The mobility of pep M24 upon electrophoresis in 10 percent sodium dodecyl sulfate pelyacrylamide gel was consistent with an average mol wt of 33,500 daltons. Amino acid analysis demonstrated a predominance of alanine, followed by glutamic acid, lysine, leucine, and aspartic acid. Pep M24 contained an estimated six to seven methionine residues and approximately ten phenylalanine residues per molecule. No other aromatic amino acids were detected. Automatic Edman degradation of pep M24 yielded the sequence of the first 29 amino acids (the amino terminal amino acid being valine) of the amino terminal region of the molecule. The detection of only one new amino acid at each step of Edman degradation confirmed the homogeneity of the purified pep M24.